GEOLOGIC OUTLINE OF THE TUSCANY-LATIUM CONTINENTAL SHELF (NORTH TYRRHENIAN SEA): SOME GEODYNAMIC IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
An old high-penetration seismic survey of the Tuscany-Latium continental shelf furnished useful information on Neogene stratigraphy, structural setting and paleogeography. The seismically penetrated stratigraphic column is composed of five seismic units which may be correlated with the tectonic and stratigraphic units of the inner Apennine belt, described in the literature. Three tectonically superposed units constitute the deformed substratum, transgressively overlain by two postorogenic sedimentary cycles. From the last diastrophic phases onward, the area underwent a very diversified tectono-sedimentary evolution, which gave origin to different structural landscapes. During the Upper Tortonian (?)-Middle Pliocene time interval the Elba-Argentario sector was subject to remarkable extensional tectonics, accompanied by important strike-slip components of mostly anti-apennine trend. Analogies with the geodynamic processes that gave rise to the inner belt Neogene basins, lead to interpret this sector of the shelf as the penetration path of the Tyrrhenian rifting within the continental area.
Keywords: Seismostratigraphy; North Tyrrhenian continental shelf; Neogene tectonics; Rifting and strike-slip tectonics; Paleogeography.